Analisis Distribusi Fasilitas Pelayanan Pendidikan Sekolah Menegah Atas (SMA) - Husain Hamka; Misilia Misilia; Ridwan Malik (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2022)
Education is an important aspect of people's life development and contributes to improving their quality of life. Education is very important as it is the basis for developing a constructive and creative mindset. The 1945 Constitution obliges the government to undertake and organize a national character education system to strengthen faith in and devotion to Almighty God and to educate the lives of its citizens. Indonesia is an educated country, but the current Indonesian education situation is still inconsistent. This has become one of the educational problems in Indonesia as education is still not evenly distributed. Governments therefore need to reflect on the importance of educational equity. This is especially true in poor and remote communities in Indonesia.